The gods of guilt ebook - Connelly, Michael (Lincoln Lawyer, 2013)
In this inspiration for the new season of the #1 Netflix show The Lincoln Lawyer , defense attorney Mickey Haller is forced to bend the law until it breaks when he's hired to defend a man accused of killing a prostitute in this suspenseful novel, the "best one yet" ( The Washington Post ).    Mickey Haller gets the text, "Call me ASAP - 187," and the California penal code for murder immediately gets his attention. Murder cases have the highest stakes and the biggest paydays, and they always mean Haller has to be at the top of his game. When Mickey learns that the victim was his own former client, a prostitute he thought he had rescued and put on the straight and narrow path, he knows he is on the hook for this one. He soon finds out that she was back in LA and back in the life. Far from saving her, Mickey may have been the one who put her in danger. Haunted by the ghosts of his past, Mickey must work tirelessly and bring all his skill to bear on a case that could mean his ultimate redemption or proof of his ultimate guilt. The Gods of Guilt shows once again why "Michael Connelly excels, easily surpassing John Grisham in the building of courtroom suspense" ( Los Angeles Times ).